Norm for Sums of Two Basic Elementary Operators - A. Bachir; F. Lombarkia; A. Segres (International Journal of Mathematics and Mathematical Sciences)
We give necessary and sufficient conditions under which the norm of basic elementary operators attains its optimal value in terms of the numerical range.